1986
DOI: 10.1002/ssu.2980020311
|View full text |Cite
|
Sign up to set email alerts
|

Minute lesions of esophageal cancer

Abstract: Fifty-four cases of minute esophageal cancer (1 cm or less in the greatest dimension) were collected and analyzed. Of these 67% were mucosal cancer and 28% were submucosal cancer. Prognosis was anticipated to be good as there was only one case of lymph node metastasis and three of vascular invasion. A lesion of 1 cm can be regarded as curable regardless of its depth of invasion. The endoscopic approach with use of a dye staining technique is useful for detection of or screening for minute esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Conversely, our sensitivity may have been somewhat underestimated because we did not biopsy small "insignificant" USLs, and other authors have shown that such lesions occasionally can contain dysplasia or carcinoma. 11,18,21,48,49 We believe that our study, as performed, clearly shows that mucosal iodine staining is a very sensitive technique for detecting the precursor and early invasive lesions of squamous esophageal carcinoma.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Conversely, our sensitivity may have been somewhat underestimated because we did not biopsy small "insignificant" USLs, and other authors have shown that such lesions occasionally can contain dysplasia or carcinoma. 11,18,21,48,49 We believe that our study, as performed, clearly shows that mucosal iodine staining is a very sensitive technique for detecting the precursor and early invasive lesions of squamous esophageal carcinoma.…”
Section: Discussionsupporting
confidence: 56%
“…In one of these studies, we found that the majority (73%) of the biopsies of high grade (moderate and severe) squamous dysplasia and all biopsies of invasive squamous cell carcinoma came from endoscopically visible mucosal lesions, but a significant minority (27%) of the sites containing high grade dysplasia could not be identified visually by routine endoscopic examination. 6 For several years, Japanese and European authors have reported that staining the esophageal mucosa with Lugol's iodine solution can make the presence and extent of squamous dysplastic and cancerous foci more clear, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but this technique has not often been used by Chinese or American endoscopists. The purpose of this study was to evaluate whether mucosal iodine staining could improve the detection and delineation of high grade squamous dysplasia and squamous cell carcinoma of the esophagus in Linxian.…”
mentioning
confidence: 99%
“…Also, we did not study patients who had negative balloon cytology examinations, and such patients might (or might not) have smaller dysplastic or invasive lesions that might be more difficult to observe. Conversely, our sensitivity may have been somewhat underestimated because we did not biopsy small "insignificant" USLs, and other authors have shown that such lesions occasionally can contain dysplasia or carcinoma 11, 18, 21, 48, 49. We believe that our study, as performed, clearly shows that mucosal iodine staining is a very sensitive technique for detecting the precursor and early invasive lesions of squamous esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 58%
“…The first use of iodine staining to detect mucosal abnormalities was by Schiller, who used this technique to highlight squamous lesions in the cervix 44. Similar staining first was used in the esophagus by Voegeli,7 Brodmerkel,38 Northmann et al,36 and Toriie et al8 In recent years, esophageal mucosal iodine staining has become common in Japan and Europe, and several studies have reported that it improves detection and border discrimination of squamous neoplastic lesions 9‐26. However, the sensitivity and specificity of the technique for identifying these lesions have not been well defined,45 and it has not been used widely in other countries, including China and the U. S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation